Watch who you trust! A structured literature review to build a typology of e-government risks - Bettina Distel; Holger Koelmann; Ralf Plattfaut; Jörg Becker (Information Systems and e-Business Management, 2022)
The information systems, e-business, and e-government literature has unanimously shown that trust and risk are antecedents of the use of information technology and technology-based services. However, a deeper understanding of the relationship between trust and risk, especially when taking into account the extensive knowledge created in fields such as organisational science and psychology, is often missing. With this article, we aim at conceptualizing risk in e-government use. Based on a structured review of the trust-related e-government literature, we derive a typology of relevant e-government risks. We analyse this typology in light of extant trust and risk literature. The typology can be used both to understand the behaviour of system or service users and to design systems and services that can be and are trusted. As such, this research can serve as a basis for future research on the role of trust and risk in designing and using e-government services. The generalizability to e-business services and information systems in general is discussed.
Keywords: 650; Risk; Trust; e-government; Literature review